Transgenic corn oil for biodiesel production via enzymatic catalysis with ethanol - Teresa M. Mata (2012)
This work aims to study the production of fatty acid ethyl esters (FAEE) from a transgenic corn oil, through transesterification using supported enzymes as catalyst (Lipozyme TL IM from Novozymes) and ethanol as reagent. First, the corn oil was characterized for its acid value (0.26 mg KOH/g oil), iodine number (127 g iodine/100 g oil), kinematic viscosity at 40 ºC (36.27 mm2 /s), density at 20 ºC (919 kg/m3 ) and water content (749 mg/kg). Second, the best operating conditions to perform the transesterification reaction were determined, by testing the following experimental conditions: oil/ alcohol molar ratio (1:3, 1:6 and 1:9), catalyst/ oil mass ratio (2.3, 2.8 and 3.3 wt%), reaction time (8 and 12 h) and reaction temperature (35 and 45 ºC). Results showed that although some of the quality parameters analyzed were out of the EN 14214:2009 standard limits (namely the kinematic viscosity, water content, acid value and group I metals) the best operating conditions for a good biodiesel quality (with 69.2 wt% of FAEE content) and the highest reaction yield (98.95 wt%) are an oil/ alcohol molar ratio of 1:6, a catalyst/ oil mass ratio of 2.8 wt%, a reaction time of 12 h and a reaction temperature of 35 ºC.